Biosafety decisions and perceived commercial risks: The role of GM-free private standards - Gruère, Guillaume P.; Sengupta, Debdatta (International Food Policy Research Institute, 2009)
We herein investigate the observed discrepancy between real and perceived commercial risks associated with the use of genetically modified (GM) products in developing countries. We focus particularly on the effects of GM-free private standards set up by food companies in Europe and other countries on biotechnology and biosafety policy decisions in food-exporting developing countries. Based on field visits made to South Africa, Namibia, and Kenya in June 2007, and secondary information from the press and various publications, we find 31 cases of interactions between private GM-free standards and biosafety policy decisions in 21 countries. Although we cannot infer the direct involvement of supermarkets and food companies in biosafety policy processes in developing countries, we find that by setting up GM-free standards, these actors are indirectly influential via their local traders, who face the possibility of exclusion if they do not comply with the standards. Organic producers? and anti-GM organizations also play a role in spreading perceptions of commercial risks that are not always justified. By comparing cases, we differentiate three types of relevant commercial risks: real risks, potential risks, and unproven risks. We then identify two critical, yet misleading, presumptions perpetuated by the various interest groups to spread the fear of potential or unproven risks: the infeasibility of non-GM product segregation and the lack of alternative buyers. We also find that information asymmetries and risk-averse behaviors related to perceived market power can help insert unfounded export concerns into biosafety or biotechnology policy decisions. The results of our analysis are used to suggest a simple framework to separate real commercial risks from others, based on five critical questions designed to aid decision makers when they face pressures to reject GM crop testing, application, consumption or use for fear of alleged export losses.